2016
DOI: 10.1016/j.jns.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of the extracorticospinal network in the brains of patients with Wilson disease

Abstract: DTI can reconstruct the network of the extracorticospinal tract. Fiber projection between subcortical nuclei was abnormal in WD patients. Damage to fiber connections may correlate with neurological symptoms in WD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…WD is an autosomal recessive defect of cellular copper export. Neurological symptoms of WD is secondary to damage to networks of the extracorticospinal tract, which includes both nuclei and fiber projections (Jadav et al., 2013; King, Walshe, Kendall, Halligan, & Hall‐Craggs, 1996; Prashanth et al., 2010; Xiang‐xue et al., 2016a). The motor asymmetry in WD may be related to asymmetry of copper deposition and damage to extracorticospinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…WD is an autosomal recessive defect of cellular copper export. Neurological symptoms of WD is secondary to damage to networks of the extracorticospinal tract, which includes both nuclei and fiber projections (Jadav et al., 2013; King, Walshe, Kendall, Halligan, & Hall‐Craggs, 1996; Prashanth et al., 2010; Xiang‐xue et al., 2016a). The motor asymmetry in WD may be related to asymmetry of copper deposition and damage to extracorticospinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Increased 64 Cu radioactivity was detected in all of brain regions in Atp7b −/− knockout mice by 21 th week of age, including regions of cortex, basal ganglia, thalamus, midbrain and brain stem and cerebellum, with highest 64 Cu radioactivity detected in cerebellum [Fig 5]. It will be useful to correlate 64 Cu radioactivity detected by [ 64 Cu]CuCl 2 PET/CT with abnormalities detected by other imaging modalities, such as abnormal fiber projection between subcortical nuclei [31], for delineation of molecular mechanism of brain tissue damage in WD patients with neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) is the most common dMRI technique. Studies have reported decreased fractional anisotropy (FA) and increased mean diffusivity (MD) in white matter and BG in Wilson's disease …”
mentioning
confidence: 99%